Sensitivity of high-resolution operational weather forecasts to the choice of the planetary boundary layer scheme - Akylas, Evangelos; Kotroni, V.; Lagouvardos, K. (My University, 2006)
In the frame of this paper three widely used planetary boundary layer parameterisations are evaluated for their ability to forecast near-surface temperature and wind speed. The analysis is based on the operational forecasts produced by the Pennsylvania State University — National Center for Atmospheric Research MM5 model over the Athens Area (Greece) during the warm period of 2002. The near-surface temperature and wind forecasts at a grid increment of 8 and 2 km over the highly complex terrain of the Athens Area are statistically verified against the available surface station observations. The results of the analysis showed that the increase in horizontal resolution (from 8 to 2 km) increases the forecast accuracy especially for temperature. As it concerns the forecast skill of each scheme it seems that the MRF scheme produces the best forecasts as it concerns the near-surface temperature while for the near-surface wind the ETA scheme gives the best results. Blackadar schemes present a consistently good behaviour for both temperature and wind forecasts.
Keywords: Planetary boundary layer parameterisations; High-resolution forecasts